Transcriptional changes in the gilthead seabream (Sparus aurata) skin in response to ultraviolet B radiation exposure - Alves, Ricardo N.; Agustí, Susana (Frontiers in Marine Science, 2022)
Solar ultraviolet B radiation (UVB) has recently been described as a relevant stressor in fish confined to aquaculture cages. In gilthead seabream (Sparus aurata), UVB exposure resulted in decreased growth, epidermal sloughing, increased oxidative stress in the skin, and induced changes in behavior, physiology, and immune system. Several molecular responses should accompany such detrimental effects; however, little is known in fish about the overall UVB-mediated changes at the transcriptional level. Thus, this study aimed to investigate the effects of UVB exposure on the global gene expression profiles of S. aurata skin through transcriptome analysis. S. aurata juveniles were exposed for 43 days to two experimental groups: 1) UVB (daily dose, 6 kJ m-2; representing levels between 5 and 7 m depth); 2) Unirradiated treatment, used as a control. The comparison of skin transcriptomes between the control and UVB treatments revealed 845 differentially expressed genes (580 up-regulated and 265 down-regulated). The reliability of the transcriptome analysis was confirmed by qRT-PCR for selected genes. Functional annotation analysis revealed that genes related to the immune system and inflammatory response, cell cycle regulation, proteasome, proteolysis, and oxidative stress response might be involved in response to the UVB exposure. In contrast, UVB exposure inhibited the expression of several genes related to growth factor activity, cell growth and differentiation, and pigmentation. p53 signaling pathway was enriched in fish exposed to UVB. Moreover, pathways involved in the immune system and inflammatory response (cytokine-cytokine receptor interaction, RIG-I-like receptor signaling pathway, and Toll-like receptor signaling pathway) were also enriched in the skin of UVB-exposed fish. UVB-induced damage and a high level of infiltration of immune-related cells were confirmed through histopathological examination. Together, our results provide noteworthy insights into the molecular changes in fish after long-term exposure to UVB. These findings will help in the future to identify biomarkers of fish reared in offshore aquaculture systems in oligotrophic and highly transparent waters.